Current Perspectives on Characteristics, Compositions, and Toxicological Effects of E-Cigarettes Containing Tobacco and Menthol/Mint Flavors - Kaur, Gurjot; Gaurav, Anshuman; Lamb, Thomas; Perkins, Melanie; Muthumalage, Thivanka; Rahman, Irfan (Frontiers in Physiology, 2020)
Electronic nicotine delivery systems/devices (ENDS) such as e-cigarettes have been made available globally, with the intent to reduce tobacco smoking. To make these products more appealing to young adults, many brands have deliberately added flavoring agents. However, these flavoring agents are shown to progressively result in lung toxicity when inhaled via e-cigarettes. While recent federal regulations have banned the sale of flavored e-cigarettes other than tobacco or menthol flavors, concerns have been raised about the health effects of even these flavors. In this review, we evaluate the current toxicological data with regard to effects upon exposure in animal models and in vitro cell culture for these popular flavorants. We have tabulated the current e-cigarette products containing these most common flavors (menthol, mint, and tobacco) in the market. We have also indicated the prevalence of tobacco and menthol-flavor use among e-cigarette users and highlighted the possible challenges and benefits that will result from new federal regulations.